Sosialisasi dan Pembuatan Biostimulan Cair Berbasis Limbah Organik untuk Mendukung Pertanian Berkelanjutan - Bahri, Syaiful; Ambarwati, Yuli; Widiarto, Sonny; Annisa, Devi Nur; Nurhasanah, Nurhasanah; Ayumi, Eksa (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The improper management of household organic waste often leads to environmental pollution and health issues. This community service program aims to educate the residents of Rejo Basuki village on processing organic waste into liquid organic fertilizer (POC) using the Biostimulant Liquid (BL) method. This method was chosen for its ability to accelerate the decomposition of organic materials without requiring a lengthy fermentation process, offering a practical and efficient waste management solution. The program was conducted through lectures and hands-on training on POC and organic pesticide production, led by lecturers from the Department of Chemistry, FMIPA, University of Lampung. The results showed that BL-based POC significantly improved soil structure, increased nutrient availability, and enhanced plant resistance to pests and diseases. Additionally, participants gained valuable knowledge on sustainable and economically beneficial organic waste management practices. This innovation is expected to be widely adopted to support sustainable and environmentally friendly agriculture.